THBS2 is Closely Related to the Poor Prognosis and Immune Cell Infiltration of Gastric Cancer - Zhang, Shiyu; Yang, Huiying; Xiang, Xuelian; Liu, Li; Huang, Huali; Tang, Guodu (Frontiers in Genetics, 2022)
Background: The potential functions of Thrombospondin 2 (THBS2) in the progression and immune infiltration of gastric cancer (GC) remain unclear. The purpose of this study was to clarify the role of THBS2 in GC prognosis and the relationship between THBS2 and GC immune cell infiltration. Material and Methods: The differential expression levels of THBS2 in the GC and cancer-adjacent tissues were identified using the TCGA databases and verified using real-time polymerase chain reaction (PCR), immunohistochemical staining and 2 datasets from Gene Expression Omnibus (GEO). THBS2 related differential genes (DEGs) were identified and used for further functional enrichment analysis and Gene Set Enrichment Analysis (GSEA). Furthermore, a THBS2-related immune infiltration analysis was also performed. Kaplan-Meier and Cox regression analyses were utilized to illustrate the effects of THBS2 on the prognosis and clinical variables of GC. Finally, a nomogram was constructed to predict the survival probability of patients with GC. Results: The THBS2 expression in GC was significantly higher than that in cancer-adjacent tissues (P<0.001), which was verified using real-time PCR, immunohistochemical staining and datasets from GEO. The 599 identified DEGs were primarily enriched in pathways related to tumorigenesis and tumor progression, including the focal adhesion pathway, signaling by vascular endothelial growth factor, and Wnt signaling. THBS2 expression was positively correlated with the enrichment of the macrophages (r = 0.590, P<0.001), which was also confirmed by immunohistochemistry; however, negatively correlated with the enrichment of Th17 cells (r = 0.260, P<0.001). The high expression of THBS2 was significantly correlated with the pathological grade (P<0.01), histological grade (P<0.05), histological type (P<0.05), T stage (P<0.001), and poor overall survival (OS) (P = 0.003) of GC. The constructed nomogram can well predict the 1-, 3-, and 5-year OS probability of patients with GC (C-index [95% confidence interval] = 0.725 [0.701–0.750]). Conclusion: THBS2 is closely related to the poor prognosis and immune infiltration of gastric cancer.